Hate Crimes against Asian Americans - Zhang, Yan (American journal of criminal justice, 2022)
Using 1992-2014 data from the National Incident-Based Reporting System (NIBRS), the present study examines the nature and characteristics of hate crimes against Asian Americans by comparing them with those of hate crimes against African Americans and Hispanics. Minority-general and minority-specific models are proposed to guide the analysis. The findings are mixed. The analyses of all victim-related and most offender-related variables show similarities of hate crimes against Asian Americans to those against African Americans and Hispanics. These findings provide support for the minority-general model. Offenders’ race and all incident-related variables of hate crimes against Asian Americans, however, differ significantly from those of hate crimes against African Americans and Hispanics. These significant differences provide support for the minority-specific model.